2009
DOI: 10.1159/000268118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Inflammatory Pain: Local Alteration in Receptors and Mediators

Abstract: Background: Inflammation is commonly associated with hyperalgesia. Ideally, this change should abate once inflammation is resolved, but this is not necessarily the case because phenotypic changes in the tissue can persist, as appears to be the case in post-infectious irritable bowel syndrome. Basically, all primary afferent neurons supplying the gut can be sensitized in response to pro-inflammatory mediators, and the mechanisms whereby hypersensitivity is initiated and maintained are, thus, of prime therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 99 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…Tissue acidosis is an important contributing factor to pain and inflammation 34 . Ion channels are critically involved in acid sensing under physiological and pathophysiological conditions 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue acidosis is an important contributing factor to pain and inflammation 34 . Ion channels are critically involved in acid sensing under physiological and pathophysiological conditions 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Tissue acidosis is an important contributing factor to pain and inflammation 34 . Ion channels are critically involved in acid sensing under physiological and pathophysiological conditions 34 . The initial functional characterizations of both human and murine TRPV3 had indicated that the channel was not activated by low pH 17 20 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, intolerance to gastric distension was documented in patients with functional dyspepsia 6,7. Some attempts have already been made to pharmacologically decrease the visceral hypersensitivity of functional GI disorders, using a number of drugs 8,9. However, the treatment was not satisfactory and the side effects could not be easily overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Some attempts have already been made to decrease pharmacologically the visceral sensitivity of functional gut disorders with a number of drugs [17], such as fedotozine, octreotide, clonidine, anti-inflammatory compounds, tricyclic antidepressants and antagonists of 5HT 3 , CRF, CCK and bradykinin, etc. However, most of these substances, although able to increase, at least experimentally, the colonic sensory threshold, are at the moment not commercially available, because being still under investigation or, if commercially available, do not represent a reliable chronic treatment for IBS pain, because of marginal clinical benefits, absence of a predominant selective effect on visceral hypersensitivity, lack of controlled studies and possible dangerous side effects during chronic treatments.…”
Section: Introductionmentioning
confidence: 99%